The Portrayal of a Black Woman‟s Perseverance in Zora Neale Hurston‟s Short Story Entitled Sweat - Asmarani, Ratna (Language Circle: Journal of Language and Literature, 2018)
This paper aims to analyze the perseverance of the black female protagonist portrayed in the short story entitled Sweat written by Zora Neale Hurston. The perseverance is used by the black female protagonist to face the domestic violence done by her abusive husband. The concept of perseverance and domestic violence are used to analyze the life of the black female protagonist. The combination of library method with its close reading, qualitative analysis, and contextual literary method focusing on intrinsic and extrinsic elements are used. The result shows that the perseverance applied by the black female protagonist enables her to survive the domestic violence leading to her freedom from her abusive husband who dies because of his own evil plan actually directed to his wife.